Drivers of population divergence and genetic variation in Elymus breviaristatus (Keng) Keng f. (Poaceae: Triticeae), an endemic perennial herb of the Qinghai-Tibet plateau - Li, Jin; Ma, Saier; Jiang, Keke; Zhang, Changbing; Liu, Wenhui; Chen, Shiyong (Frontiers in Ecology and Evolution, 2022)
Elymus breviaristatus, a rare grass species with excellent resistance and ecological importance, is narrowly distributed on the Qinghai-Tibet Plateau (QTP). Populations of E. breviaristatus are declining due to habitat fragmentation, and thus far, characteristics of genetic differentiation and adaptive responses to climate change remain poorly understood in this species. Here, we explored the genetic structure of 18 natural populations (269 individuals) in the transition zone between Tibet and the Hengduan Mountains using 15 expressed sequence tag (EST)-SSR primer pairs and identified possible barriers to gene flow that might have caused genetic discontinuities. Additional analyses were performed to identify the environmental factors affecting genetic diversity and to test whether the patterns of genetic variation among populations were more consistent with the isolation by distance (IBD) or isolation by environment (IBE) model. Multiple measures of genetic diversity revealed that intra-population genetic variation was low, while inter-population genetic variation was high. Clustering, structure, and principal coordinate analyses identified three genetic groups: (a) Eastern Qamdo, (b) Nagqu and Western Qamdo, and (c) Lhasa and Nyingchi. A clear physical barrier to gene flow was formed by the Yarlung Zangbo Grand Canyon and the Tanggula Mountains. We found that both IBD and IBE contributed to the observed patterns of genetic variation, indicating that the process of population differentiation was affected by complex mechanisms. In addition, precipitation-related variables, soil phosphorus content and soil K:P ratio significantly affected population genetic variation. Overall, our results emphasized the genetic fragility of E. breviaristatus populations and showed that this species requires attention, as future climate changes and human activities may further threaten its survival. In addition, the genetic differences among E. breviaristatus populations should be considered when formulating conservation measures for E. breviaristatus populations in the study area.